Assessment of Power System Risk in Cyber-Attacks in View of the Role Protection Systems - Hui Hwang Goh; Sy yi Sim; Omar Abdi Mohamed; Ahmed Farah Mohamed; Chin Wan Ling; Qing Shi Chua; Kai Chen Goh (Institute of Advanced Engineering and Science, 2017)
This paper presents a risk assessment method for assessing the cyber security of power systems in view of the role of protection systems. This paper examines the collision of transmission and bus line protection systems positioned in substations on the cyber-physical performance of the power systems. The projected method simulates the physical feedback of power systems to hateful attacks on protection system settings and parameters. The relationship between protection device settings, protection logic, and circuit breaker logic is analyzed. The expected load reduction (ELC) indicator is used in this paper to determine potential losses in the system due to cyber attacks. The Monte Carlo simulation is used to calculate ELC’s account to assess the capabilities of the attackers and bus arrangements are changed. The influence of the projected risk assessment method is illustrated by the use of the 9-bus system and the IEEE-68 bus system.